Compósitos à base de PVDF pós-industrial e cargas condutoras - Leão, Ariadne Gonçalves de (2017)
PVDF is a versatile engineering polymer, and finds applications in different industrial sectors, such as chemical, mechanical, electronic, oil and gas, etc. Especially in the last one, the amount of PVDF residue generated from flexible pipes manufacturing is high. The PVDF has been widely studied due to its four crystalline phases with distinct characteristics, of which the beta phase (β) is of great scientific and technological interest due to its piezo and pyroelectric properties. In this work, in order to contribute to sustainability and give the PVDF residue a new applicability, PVDF based composites were manufactured with the polymer in the non-polar alpha phase (α) loaded with carbon black particles, polyaniline and graphite, added to increase the electrical conductivity of the polymer. The results of XRD and FTIR showed that the insertion of different conductive charges did not induce the formation of β phase in the polymer, however, there was an increase in the electrical conductivity (AC) of the composites since the electrical percolation threshold was achieved. The thermal properties of the composites were evaluated by TGA and DSC, the mechanical properties by DMA and the morphology by SEM. In addition, the rheological behavior and the electromagnetic interference shielding characteristics of the composites were investigated.